Stability-enhanced alginic acid-keratin-based double-coated nanoparticles as well as preparation method and application thereof

Stability-enhanced alginate-keratinyl double-coated nanoparticles are formed through controlled enzymatic lysis and pH regulation technology, which solves the problem of poor stability of the protein-based nanodelivery system, and achieves high bioactive molecules loading and stability, which is suitable for oral nanodelivery systems.

CN119548474AActive Publication Date: 2025-03-04INST OF AGRO FOOD SCI & TECH CHINESE ACADEMY OF AGRI SCI

Patent Information

Application Number
CN202411582004.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-04
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing protein-based nanodelivery system has poor stability, resulting in low encapsulation rate of bioactive molecules, premature leakage and degradation, limiting its bioavailability and application.

Method used

Through controlled enzymatic lysis and pH regulation technology, keratin nanoparticles with regular shape and good dispersion are self-assembled to form stable-enhanced alginate-keratin double-coated nanoparticles through the calcium alginate coated layer, thereby improving the load rate and stability of biologically active molecules.

Benefits of technology

It has achieved a high load rate of bioactive molecules (up to 92.0-95.6%), improved the resolubility and environmental stability of nanoparticles, enhanced the stability and bioavailability of bioactive molecules, and is suitable for oral nanodelivery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548474A_ABST
    Figure CN119548474A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of stability-enhanced alginic acid-keratin-based double-coated nanoparticles. The preparation method comprises the following steps: carrying out controllable enzymolysis, enzyme deactivation, centrifugation and freeze-drying on keratin to obtain keratin nanoparticles formed by self-assembly; dispersing the keratin nanoparticles in an acidic buffer solution to carry out structure development, adding bioactive molecules, and adjusting the pH to be neutral to recombine and close the keratin nanoparticle structure to obtain a keratin nanoparticle solution loaded with the bioactive molecules; the preparation method comprises the following steps: taking keratin as a template, dispersing the keratin into a sodium alginate solution, dropwise adding into a calcium chloride solution, cross-linking to form a calcium alginate shell, dialyzing or centrifuging to remove free bioactive molecules, and freeze-drying to obtain the bioactive molecule loaded alginic acid-keratin-based double-coated nanoparticles. The invention also discloses double-coated nanoparticles and application thereof, through controllable enzymolysis and pH regulation and control, the self-assembly and bioactive molecule encapsulation of the keratin nanoparticles are improved, and the double-coated nanoparticles with regular shape, good dispersibility, good redissolvability and good environmental stability are formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-biomaterials, and in particular to stability-enhanced alginate-keratin-based double-coated nanoparticles and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of in vitro screening technology, more and more natural bioactive molecules have been found to have nutritional and disease regulation functions and have been widely used in food, health care products and pharmaceutical fields, such as protein peptides, polyphenols and flavonoids. Studies have shown that these bioactive molecules have shown application potential in anti-oxidation, anti-cancer, anti-inflammatory and other aspects. However, most bioactive molecules still have problems such as poor water solubility, easy enzymatic degradation, environmental instability (storage, heat, extreme pH, etc.) and low biomembrane permeability, which greatly limit their bioavailability and applicability. Therefore, researchers have developed a variety of delivery systems to improve the physicochemical properties and bioavailability of bioactive molecules. Among them, nanoparticles, as an effective delivery carrier, can significantly improve the solubility and stability of bioactive molecules, and achieve targeted delivery and controlled release. Among the many encapsulation wall materials, proteins, as a natural polymer, are widely used in nano-delivery systems due to their biocompatibility, biodegradability and low toxicity. However, most proteins have poor stability, resulting in low encapsulation efficiency of bioactive molecules, premature leakage and degradation. For example, the patent with application number 202110562800.2 discloses a feather keratin / sodium alginate microgel drug delivery system and its preparation method and application. Although it increases the drug loading and reduces the drug leakage rate, the maximum drug loading is only 65%, and it is easily degraded in an acidic environment and has poor stability. Therefore, how to increase the drug loading, improve the stability of the protein-based nano-delivery system, solve the problems of high aggregation, poor water solubility, and easy degradation of bioactive molecules, so as to improve the bioavailability of bioactive molecules, is still a technical bottleneck and research hotspot that needs to be solved in this field. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0004] Another object of the present invention is to provide a method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles, which can reduce keratin aggregation and self-assemble to form nanoparticles with regular shape and good dispersibility through controlled enzymatic hydrolysis and pH regulation technology, with an average particle size of about 123 nm; pH regulation (from acidic to neutral) can make keratin nanoparticles present an "open-closed" structural change, which is conducive to the encapsulation of bioactive molecules. By further establishing a calcium alginate coating layer, spherical nanoparticles of uniform size can be formed, with an average particle size of about 170-173 nm, and a bioactive molecule encapsulation rate of 92.0-95.6%. The preparation method of the present invention has low raw material cost and a wide range of sources, improves production efficiency, and has no pollution from introduced chemical reagents during the entire production process.

[0005] Still another object of the present invention is to provide a stability-enhanced alginate-keratin-based double-coated nanoparticles having a high bioactive molecule encapsulation rate, regularly shaped spherical nanoparticles with an average particle size of 170-173 nm, good resolubility and environmental stability (such as heat treatment and low-temperature storage), and their responsiveness to changes in gastrointestinal pH can significantly improve the stability of bioactive molecules.

[0006] Another object of the present invention is to provide an application of stability-enhanced alginate-keratin-based double-coated nanoparticles in the preparation of bioactive molecule nano-delivery carriers. The stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention have good encapsulation effects on both hydrophilic molecules (insulin) and hydrophobic molecules (resveratrol) in the preparation of bioactive molecule nano-delivery carriers, and can be widely used in the encapsulation and delivery of bioactive molecules, including but not limited to oral nano-delivery systems.

[0007] In order to achieve these objects and other advantages according to the present invention, a method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles is provided, which comprises the following steps: Step 1: Degrading keratin with a controlled enzyme, inactivating the enzyme, centrifuging, and freeze-drying to obtain self-assembled keratin nanoparticles; Step 2: dispersing the keratin nanoparticles obtained in step 1 in an acidic buffer for structural development, adding bioactive molecules, stirring, and adjusting the pH value to neutral to allow the keratin structure to be reorganized and closed to obtain a keratin nanoparticle solution loaded with bioactive molecules; Step 3: Disperse the keratin nanoparticles loaded with bioactive molecules obtained in step 2 in a sodium alginate solution, add the mixture dropwise into a calcium chloride solution to cross-link and form a calcium alginate shell, perform dialysis or centrifugation to remove free bioactive molecules, and freeze-dry to obtain alginate-keratin double-coated nanoparticles loaded with bioactive molecules.

[0008] Preferably, step one specifically includes: S11, evenly dispersing keratin in phosphate buffer, stirring for 12 to 16 hours for full hydration, adjusting the pH to 8.5, the temperature to 50 to 60 °C, the enzyme dosage to 5000-8000 U / g, and controlling the degree of hydrolysis to 5 to 15% for enzymatic degradation; S12. After the enzymatic hydrolysis, heat at 95°C for 3 min to inactivate the enzyme, adjust the pH to 7.0, centrifuge at 6000-8000×g for 20-30 min, and freeze-dry to obtain self-assembled keratin nanoparticles.

[0009] Preferably, step 2 specifically includes: S21, dispersing the keratin nanoparticles obtained in step 1 in a phosphate buffer solution with a pH of 1.5 to 3.0, and stirring at 600 to 800 rpm for 1 to 2 h to develop the structure; S22, adding bioactive molecules, continuing stirring for 1 to 2 hours, adjusting the pH to 7.0, and continuing stirring for 1 to 2 hours to reorganize and close the structure to form a keratin nanoparticle solution loaded with bioactive molecules.

[0010] Preferably, step three specifically includes: S31, adding the keratin nanoparticle solution loaded with bioactive molecules obtained in step 2 dropwise into an equal volume of a sodium alginate solution having a mass volume concentration of 1 to 3%, and continuously stirring for 1 to 2 hours to obtain a mixed solution; S32. The mixed solution is added dropwise into an equal volume of 2-10 mM calcium chloride solution, and after continuous stirring for 1-2 h, free bioactive molecules are removed by dialysis or centrifugation, and freeze-dried to obtain alginate-keratin-based double-coated nanoparticles loaded with bioactive molecules.

[0011] Preferably, the bioactive molecule is insulin or resveratrol.

[0012] Preferably, in S11, the temperature is 55° C. and the enzyme dosage is 6000 U / g; in S12, freeze-drying specifically comprises: freeze-drying the enzymatic hydrolysis supernatant at -76° C. and 0.009 mbar for 72 h.

[0013] Preferably, the mass ratio of keratin nanoparticles to biological activity is 2:1 or 25:1, respectively.

[0014] Preferably, S32 specifically comprises: adding the mixed solution dropwise into an equal volume of 4 mM calcium chloride solution, stirring continuously at 700 rpm for 1 h, dialyzing with a dialysis bag with a molecular weight cutoff of 7 kDa to remove free bioactive molecules, the dialysis time being ≥36 h, and freeze-drying at -76°C and 0.009 mbar for 72 h to obtain alginate-keratin-based double-coated nanoparticles loaded with bioactive molecules.

[0015] The object of the present invention can be further achieved by stability-enhanced alginate-keratin-based double-coated nanoparticles.

[0016] Still another object of the present invention is to achieve the purpose by using the stability-enhanced alginate-keratin-based double-coated nanoparticles in the preparation of nano-delivery carriers for bioactive molecules.

[0017] The present invention has at least the following beneficial effects: First, the preparation method of the stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention uses controlled enzymatic hydrolysis and pH control technology. Moderate enzymatic hydrolysis can reduce keratin aggregation and self-assemble to form nanoparticles with regular shape and good dispersion, with an average particle size of about 123 nm; pH control (from acidic to neutral) can make keratin nanoparticles present an "open-closed" structural change, which is conducive to the encapsulation of bioactive molecules. By further establishing a calcium alginate coating layer, spherical nanoparticles of uniform size can be formed, with an average particle size of about 170-173nm, and a bioactive molecule encapsulation rate of 92.0-95.6%. The preparation method of the present invention has low raw material cost and a wide source, which improves production efficiency, and there is no pollution from chemical reagents introduced into the whole production process.

[0018] Second, the stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention have a high bioactive molecule encapsulation rate, are regularly shaped spherical nanoparticles, have an average particle size of 170-173 nm, have good solubility and environmental stability (such as heat treatment and low-temperature storage), and their responsiveness to changes in gastrointestinal pH can significantly improve the stability of bioactive molecules.

[0019] Third, the stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention have good encapsulation effects on both hydrophilic molecules (insulin) and hydrophobic molecules (resveratrol) in the preparation of bioactive molecule nano-delivery carriers, and can be widely used in the encapsulation and delivery of bioactive molecules, including but not limited to oral nano-delivery systems.

[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The flowchart is a method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention; Figure 2 The theoretical structure diagram of the stability-enhanced alginate-keratin-based double-coated nanoparticles of the present invention; Figure 3 A is a microstructure of keratin nanoparticles self-assembled by optimal enzymatic hydrolysis (5% hydrolysis degree) in Example 1 of the present invention, B is a microstructure of keratin nanoparticles self-assembled by enzymatic hydrolysis (15% hydrolysis degree) in Example 3, C is a microstructure of keratin nanoparticles formed without enzymatic hydrolysis in Comparative Example 1, and D is a microstructure of keratin nanoparticles self-assembled by excessive enzymatic hydrolysis (20% hydrolysis degree) in Comparative Example 2; Figure 4 A is an "open" diagram of the keratin nanoparticle structure in Example 1 of the present invention under acidic conditions (pH=2.0); B is a "closed" diagram of the keratin nanoparticle structure in Example 1 under neutral conditions (pH=7.0); Figure 5 The figure is a comparison of the particle size analysis and re-dissolution of the insulin-loaded keratin nanoparticles (KNP-INS) obtained by pH regulation in step 2 of Example 1 of the present invention and the insulin-loaded keratin nanoparticles (KNP-INS-pH7) obtained in Comparative Example 3 without pH regulation; Figure 6 : are microstructure diagrams of different substances in Example 1 of the present invention, wherein A is a microstructure diagram of insulin (INS), B is a microstructure diagram of calcium alginate-insulin (ALG-INS); C is a microstructure diagram of keratin-insulin (KNP-INS); and D is a microstructure diagram of calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS); Figure 7 The figures are comparison diagrams of the solubility results and particle size analysis diagrams of nanoparticles of different substances in Example 1 of the present invention, wherein A is a comparison diagram of the solubility results of INS, ALG-INS, KNP-INS, and ALG-KNP-INS, and B is a particle size analysis diagram of INS, ALG-INS, KNP-INS, and ALG-KNP-INS; Figure 8 This is an infrared structural analysis diagram of nanoparticles of different substances in Example 1 of the present invention; Fig. 9 This is a graph showing the stability results of nanoparticles of different substances in Example 1 of the present invention when treated at 80° C. for 0-60 min; Fig.10This is a graph showing the stability results of nanoparticles of different substances in Example 1 of the present invention stored at 4° C. for 0-28 days; Fig.11 This is the appearance diagram of ALG-KNP-INS prepared in Example 1 of the present invention as the pH of the gastrointestinal tract changes; Fig.12 This is a graph showing the gastrointestinal stability results of INS and ALG-KNP-INS in Example 1 of the present invention; Fig.13 A is a graph showing the solubility results of resveratrol (RES) and calcium alginate-keratin-resveratrol (ALG-KNP-RES) nanoparticles in Example 2 of the present invention, B is a graph showing the particle size analysis of calcium alginate-keratin-resveratrol (ALG-KNP-RES) nanoparticles, and C is a graph showing the microstructure of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES); Fig.14 A is a transmembrane transport diagram of ALG-KNP-INS in Example 1 of the present invention; B is a cellular absorption diagram of ALG-KNP-INS provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0025] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0026] Keratin is the third most abundant natural polymer after cellulose and chitin. It has good biocompatibility, biodegradability and low toxicity and has been widely used in the field of biomedical materials. Keratin is rich in cystine (>7 mol%), and its abundant disulfide bonds provide keratin with a highly stable structure. Studies have shown that keratin has good aqueous solution stability and resistance to traditional protease degradation. At the same time, they can penetrate kidney and liver cells, showing good cell adhesion and proliferation and permeability, showing great application potential in the field of nano-delivery systems. Alginate, as a natural polysaccharide, has good gelation, pH sensitivity and mucus adhesion. It is a high-quality carrier excipient and has been used in the preparation of carriers such as nanoparticles, liposomes, capsules, tablets, hydrogels and microspheres. Alginate coating can further protect the loaded bioactive molecules from gastrointestinal pH and enzyme degradation. At present, nanoparticle preparation technologies are mainly divided into three categories: physical methods (such as spray drying and anti-solvent methods), chemical methods (such as covalent bond cross-linking) and enzymatic methods. However, most processes have disadvantages such as chemical reagent residues, long process time, complex operation, high cost and uneven product quality. For example, the anti-solvent precipitation method will cause chemical reagent residues; the covalent bond cross-linking method is time-consuming, the particle size is large and involves chemical reagent residues; the thermal aggregation method has high energy consumption, etc. Therefore, how to provide a green and efficient stability-enhanced nanoparticle preparation technology for bioactive molecule encapsulation and delivery has become an urgent problem to be solved in this field.

[0027] In order to improve the shortcomings of the bioactive molecule delivery system such as poor solubility, poor stability, and low bioavailability, the present invention is based on keratin materials and combines controllable enzymatic modification and pH regulation technology to achieve regulation of the self-assembly behavior of keratin molecules, so as to improve the dispersibility of keratin nanoparticles and the encapsulation rate of bioactive molecules, and further forms a calcium alginate coating layer through gel technology to construct a double-coated nanoparticle structure, thereby effectively enhancing the processing / storage stability of the bioactive molecule delivery system, and achieving gastrointestinal pH-responsive structural changes to enhance its delivery efficiency and bioavailability.

[0028] The present invention utilizes controlled enzymatic hydrolysis and pH regulation technology to improve the microstructure and self-assembly behavior of keratin molecules, prepares keratin nanoparticles with regular shape and good dispersion to encapsulate bioactive molecules, and then establishes a calcium alginate coating layer through gel technology to form alginate-keratin-based double-coated nanoparticles with enhanced bioactive molecule encapsulation ability and stability. The technical process of the present invention is as follows: Figure 1As shown. The present invention uses controlled enzymatic hydrolysis technology and keratinase to moderately open the disulfide bonds and peptide bonds of keratin molecules, reduce the degree of cross-linking of keratin molecules, reduce the aggregation behavior of keratin molecules, and self-assemble to form keratin nanoparticles with good dispersion and regular shape. The present invention uses pH control technology to break the forces between keratin molecules (such as electrostatic interactions and hydrogen bonds) in an acidic environment, and the keratin nanoparticles present a structurally developed state; accompanied by adjustment to a neutral environment, the keratin molecules achieve structural reorganization and closure. This "development-closure" process can promote the encapsulation of bioactive molecules. The present invention uses sodium alginate gel technology to form a calcium alginate shell on the outside of the nanoparticles through cross-linking of sodium alginate and calcium ions, construct an alginate-keratin-based double-coated nanoparticle system, and improve the stability of bioactive molecules; based on the pH sensitivity of alginate (structural contraction in an acidic environment), the "aggregation-redispersion" structural responsiveness of the double-coated nanoparticles in the gastrointestinal environment is achieved, thereby improving its digestion stability. The theoretical structure diagram of the stability-enhanced alginate-keratin-based double-coated nanoparticles prepared by the present invention is shown in Figure 2 shown.

[0029] In the present invention, ALG represents calcium alginate, KNP represents keratin nanoparticles, INS represents insulin, and RES represents resveratrol.

[0030] Example 1 A method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles comprises the following steps: Step 1. Keratin was uniformly dispersed in a phosphate buffer (pH = 7.0, 10 mM) at a concentration of 5% (w / v), stirred at 700 rpm for 12 h for full hydration, and then the pH of the buffer was adjusted to 8.5 with a NaOH solution (1 M) for enzymatic hydrolysis. The enzymatic hydrolysis temperature was 55°C, the enzyme dosage was 6000 U / g, and the degree of keratin hydrolysis was controlled at 5%. After the enzymatic hydrolysis, the keratin hydrolyzate was heated at 95°C for 3 min to inactivate the enzyme, and then the pH was adjusted to 7.0 with a HCl solution (1 M), and centrifuged at 8000 × g for 20 min to obtain self-assembled keratin nanoparticles (KNPs), which were freeze-dried at -76°C and 0.009 mbar for 72 h. The average particle size of the obtained keratin nanoparticles was 123 ± 7.0 nm, and the microscopic morphology was as follows: Figure 3 As shown in A; Step 2: Disperse 20 mg of keratin nanoparticles in 2 mL of phosphate buffer (pH = 2.0, 10 mM), stir at 700 rpm for 1 h to develop the structure, add 2 mL of insulin solution (5 mg / mL, dissolved in 0.01 M HCl) dropwise and continue stirring at 700 rpm for 1 h. Subsequently, adjust the pH to 7.0 using NaOH solution (1 M), and continue stirring for 2 h to restructure and close the structure to form an insulin-loaded keratin nanoparticle solution (KNP-INS). The average particle size of the obtained KNP-INS is 141.2 ± 12.5 nm. The "development-closure" process of the keratin nanoparticle structure is as follows: Figure 4 As shown, Figure 4 Figure A is the development diagram of the keratin nanoparticle structure under acidic conditions (pH=2). Figure 4 B is a closed diagram of the keratin nanoparticle structure under neutral conditions (pH = 7); Step 3: KNP-INS was added dropwise to an equal volume of sodium alginate solution (1%, w / v), stirred at 700 rpm for 1 h, and then the mixture was added dropwise to an equal volume of CaCl 2 Solution (4 mM) was stirred continuously for 1 h to form alginate-keratin-based double-coated nanoparticles loaded with insulin: calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS). Free insulin was removed by dialyzing using a dialysis bag with a molecular weight cutoff of 7 kDa, and the dialysis time was ≥36 h.

[0031] Among them, the microscopic structure of insulin (INS) is shown in the figure Figure 6 The microstructure of calcium alginate-insulin (ALG-INS) is shown in Figure 6B; the microstructure of keratin-insulin (KNP-INS) is shown in Figure 6A. Figure 6 As shown in C; the microstructure of calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) is as follows Figure 6 As shown in D, the insulin encapsulation efficiency was 92.0±1.2%.

[0032] Insulin (INS), insulin-loaded keratin nanoparticles (KNP-INS) and insulin-loaded calcium alginate particles (ALG-INS) were used as controls. ALG-INS was prepared according to steps 2 and 3 in Example 1, except that the keratin nanoparticle dispersion was replaced with complete phosphate buffer without keratin.

[0033] Example 2 A method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles comprises the following steps: Step 1: Keratin was uniformly dispersed in a phosphate buffer (pH 7.0, 10 mM) at a concentration of 5% (w / v), stirred at 700 rpm for 12 h for full hydration, and then the pH of the buffer was adjusted to 8.5 with a NaOH solution (1 M) for enzymatic hydrolysis. The enzymatic hydrolysis temperature was 55°C, the enzyme dosage was 6000 U / g, and the degree of keratin hydrolysis was controlled at 5%. After the enzymatic hydrolysis, the keratin hydrolyzate was heated at 95°C for 3 min to inactivate the enzyme, and then the pH was adjusted to 7.0 with a HCl solution (1 M), and centrifuged at 8000 × g for 20 min to obtain self-assembled keratin nanoparticles (KNPs), which were freeze-dried at -76°C and 0.009 mbar for 72 h. Step 2: Disperse 20 mg of keratin nanoparticles in 2 mL of phosphate buffer (pH 2.0, 10 mM), stir at 700 rpm for 1 h for structural development, add 80 μL of resveratrol (RES) solution (10 mg / mL, dissolved in ethanol) dropwise and continue stirring at 700 rpm for 1 h, then adjust the pH to 7.0 using NaOH solution (1 M), and continue stirring for 2 h for structural reorganization and closure to form a resveratrol-loaded keratin nanoparticle solution (KNP-RES); Step 3: KNP-RES was added dropwise to an equal volume of sodium alginate solution (1%, w / v), stirred at 700 rpm for 1 h, and then the mixture was added dropwise to an equal volume of CaCl 2 Solution (4 mM) was stirred continuously for 1 h to form alginate-keratin-based double-coated nanoparticles loaded with resveratrol: calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES). Free resveratrol was removed by centrifugation at 8000 × g for 20 min.

[0034] Among them, the microstructure of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES) is as follows Fig.13 As shown in C, the particle size analysis of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES) is shown in Fig.13 As shown in B, the resolubility results of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES) are shown in Fig.13 As shown in A, the resveratrol encapsulation efficiency is 95.61±1.44%.

[0035] Example 3 The difference between this embodiment and Example 1 is that in step 1, the degree of keratin hydrolysis is controlled at 15%.

[0036] Comparative Example 1 The difference between this embodiment and Example 1 is that no enzymatic hydrolysis is performed in step 1.

[0037] Comparative Example 2 The difference between this embodiment and Example 1 is that in step 1, the degree of keratin hydrolysis is controlled at 20%. The microscopic morphology of the self-assembled keratin nanoparticles prepared in Example 1, Comparative Example 1 and Comparative Example 2 is as follows: Figure 3 As shown, Figure 3 A is the microscopic morphology of keratin nanoparticles prepared by controlled enzymatic hydrolysis (5% hydrolysis degree) in Example 1. Figure 3 B is the microscopic morphology of keratin nanoparticles obtained by controlled enzymatic hydrolysis (15% hydrolysis degree) in Example 3. Figure 3 C in the middle is the microscopic morphology of keratin nanoparticles produced without enzymatic hydrolysis. Figure 3 Figure D shows the microscopic morphology of keratin nanoparticles obtained by excessive enzymatic hydrolysis (20%). Figure 3 It can be seen that the average particle size of keratin nanoparticles formed without enzymatic hydrolysis is micrometer-level, with a compact structure and irregular shape; the keratin particles formed by excessive enzymatic hydrolysis are irregular in shape and easy to aggregate tightly; the average particle size of keratin nanoparticles formed by optimal enzymatic hydrolysis with a hydrolysis degree of 5% is 123 ± 7.0 nm, showing a uniformly distributed hollow sphere. Controlled enzymatic hydrolysis can effectively prepare spherical keratin nanoparticles with regular shape and uniform distribution.

[0038] Comparative Example 3 The difference between it and Example 1 is that: Step 2: Disperse 20 mg of keratin nanoparticles in 2 mL of phosphate buffer (pH=7.0, 10 mM), stir at 700 rpm for 1 h, add 2 mL of insulin solution (5 mg / mL, dissolved in 0.01 M HCl) dropwise and continue stirring at 700 rpm for 1 h to form an insulin-loaded keratin nanoparticle solution (KNP-INS-pH7).

[0039] By comparing Example 1 with Comparative Example 3, the results of particle size analysis and resolubility analysis are as follows: Figure 5 As shown in the figure, the average particle size of KNP-INS prepared by pH control in step 2 of Example 1 of the present invention is 141.2 ± 12.5 nm, and the reconstituted solution is clear and transparent. Figure 6As can be seen from Figure C, KNP-INS presents a compact granular structure with good dispersion, which effectively improves insulin (INS) aggregation, reduces particle size, and improves dispersion; the average particle size of KNP-INS-pH7 prepared without pH regulation is 316.0 ± 53.1 nm, the reconstituted solution is relatively turbid, and the reconstitution is poor; pH regulation can effectively reduce the particle size of keratin nanoparticles loaded with insulin and improve the reconstitution of KNP-INS. In addition, Figure 4 As shown in the figure, through pH regulation, the structure of keratin nanoparticles is completely opened at pH = 2.0, presenting a network structure; when the pH is adjusted back to 7.0, keratin reorganizes and closes to form nanoparticles with a compact structure. This "opening-closing" process can promote the encapsulation of bioactive molecules.

[0040] Performance Experiment 1. Microscopic morphology of nanoparticles: The microscopic morphology of the nanoparticles was observed using a transmission electron microscope (TEM). The microscopic morphology of the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 is as follows: Figure 6 As shown in D, from Figure 6 It can be concluded from Figure D that ALG-KNP-INS presents a regular spherical shape with good dispersibility. The microstructure of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES) prepared in Example 2 is shown in Figure 3. Fig.13 As shown in C, from Fig.13 It can be concluded from Figure C that ALG-KNP-RES presents a regular spherical shape with good dispersion.

[0041] 2. Nanoparticle size analysis and solubility: The particle size of the nanoparticles was analyzed using a Malvern ZetaSizer; the solubility was determined based on the dispersion clarity of the nanoparticle aqueous dispersion (1 mg / mL).

[0042] The particle size analysis results of the insulin-loaded alginate-keratin-based double-coated nanoparticles (ALG-KNP-INS) prepared in Example 1 and the particle size comparison results of the alginate-keratin-based double-coated nanoparticles (ALG-KNP-INS) and INS, ALG-INS, and KNP-INS are shown in FIG. Figure 7 As shown in B, from Figure 7 In Figure B, it can be concluded that the average particle size of ALG-KNP-INS is 173.0 ± 14.4 nm; the solubility results of calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1, and the solubility comparison results thereof with INS, ALG-INS, and KNP-INS are as follows: Figure 7 As shown in A, from Figure 7As shown in Figure A, the ALG-KNP-INS reconstituted solution is clear and transparent, and has good reconstitution properties. Fig.13 As shown in B, the resolubility results are shown in Fig.13 As shown in A, from Fig.13 It can be concluded that the average particle size of calcium alginate-keratin-resveratrol nanoparticles (ALG-KNP-RES) is 170.5±11.3 nm, the reconstituted solution is clear and transparent, the reconstituted solubility is good, and the resveratrol encapsulation rate is 95.61±1.44%. The alginate-keratin-based double coating layer can also efficiently encapsulate the hydrophobic molecule resveratrol, which can effectively reduce the particle size of resveratrol and improve its dispersibility and solubility in aqueous solution.

[0043] 3. Analysis of chemical structure of nanoparticles: The chemical structure of the nanoparticles was analyzed by Fourier transform infrared spectroscopy (FTIR) spectrometer. The infrared structure analysis of the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 is shown in FIG. Figure 8 As shown, from Figure 8 It can be seen that the FTIR analysis results show that the infrared spectrum of ALG-KNP-INS has characteristic peaks of alginate and has an effective calcium alginate coating layer.

[0044] 4. Thermal stability and storage stability: Thermal stability: Take the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 as an example: the aqueous dispersion of ALG-KNP-INS (1 mg / mL) was heated in a water bath at 80°C for 0 to 60 minutes, then cooled to room temperature with running water, and the insulin was quantitatively analyzed by HPLC. The thermal stability of the nanoparticles was evaluated based on the insulin retention rate after a certain period of heat treatment. The analysis results are shown in Figure 2. Fig. 9 shown.

[0045] Storage stability: Taking the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 as an example: the aqueous dispersion of ALG-KNP-INS (1 mg / mL) was stored at 4°C for 0-28 days, and then the insulin was quantitatively analyzed by HPLC. The storage stability of the nanoparticles was evaluated based on the insulin retention rate after a certain period of low-temperature storage. The analysis results are shown in Figure 2. Fig.10 shown.

[0046] from Fig. 9 and Fig.10It can be seen that after thermal stability and storage stability analysis, the results show that during heat treatment (80℃, 0-60 min) and low-temperature storage (4℃, 0-28 days), the protective effect of ALG-KNP-INS on insulin was significantly enhanced, and its insulin retention rate was significantly higher than that of INS, KNP-INS and ALG-INS. After heat treatment for 30 minutes and refrigeration for 3 weeks, it still had an insulin retention rate of more than 90%.

[0047] 5. Gastrointestinal digestion stability: Take the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 as an example: Gastric digestion: The sample was dispersed in a pH 2.0 HCl solution to a final insulin concentration of 1 mg / mL, and 1.6 mg / mL of pepsin was added. The digestion was simulated in a 37°C water bath with a stirring speed of 250 rpm for 90 min. At the end of gastric digestion, the pH was adjusted to 6.8 with 1 M NaOH and quickly cooled in an ice bath.

[0048] Intestinal digestion: After the gastric digestion, the sample pH was adjusted to 6.8 with NaOH (1 M) and mixed with an equal volume of pancreatic enzyme solution (10 mg / mL, dissolved in pH 6.8, 10 mM phosphate buffer). Digestion was then continued for 120 min in a 37°C water bath with a stirring rate of 250 rpm. Digestion samples were collected at predetermined time points (30, 60, and 120 min) and rapidly cooled. The particle size changes of the digestion samples without enzyme addition were observed, and the results are shown in Figure 2. Fig.11 As shown, the insulin stability analysis was performed on the enzymatically digested samples using the SDS-PAGE method. Fig.12 shown.

[0049] The results of simulated gastrointestinal digestion showed that ALG-KNP-INS had pH-responsive structural changes to the gastrointestinal environment ( Fig.11 ), ALG-KNP-INS aggregates first and then disperses as the pH increases from 2.0 to 6.8, which can potentially block the degradation of the loaded insulin by proteases. Fig.12 The results showed that ALG-KNP-INS can effectively alleviate the degradation of insulin by gastrointestinal proteases. Compared with other forms, the double coating of calcium alginate-keratin (ALG-KNP) can effectively improve insulin aggregation, reduce particle size, improve its dispersibility and solubility, and significantly improve the stability of insulin during heating, storage and digestion.

[0050] 6. Transmembrane transport and cellular absorption: Take the calcium alginate-keratin-insulin nanoparticles (ALG-KNP-INS) prepared in Example 1 as an example: Caco2 cells were used to construct a monolayer cell membrane to simulate intestinal epithelial cells, and the transmembrane transport ability of nanoparticles was analyzed (the results are shown in Fig.14 The ability of nanoparticles to deliver insulin (INS) to cells was evaluated by co-culturing Caco2 cells and nanoparticles. Insulin (INS) was labeled with fluorescein, and its cellular uptake was observed using confocal laser scanning microscopy (CLSM) (the results are shown in Fig.14 (shown in B).

[0051] Caco2 cell experiments showed that ALG-KNP-INS can pass through the Caco2 monolayer cell membrane ( Fig.14 Middle A); Cell absorption experiments showed that ALG-KNP-INS has the ability to deliver INS to cells ( Fig.14 Middle B). The double coating of ALG-KNP has certain application potential in improving the aggregation, water solubility, stability and transmembrane delivery of bioactive molecules.

[0052] Traditional bioactive molecules such as resveratrol and insulin have the disadvantages of poor water solubility, environmental degradation, poor intestinal absorption, and poor transmembrane permeability, resulting in poor storage stability and low bioavailability. The present invention uses controlled enzymatic hydrolysis and pH control technology to regulate the self-assembly behavior of keratin molecules, effectively solves the problems of poor water solubility and easy aggregation of keratin, improves the encapsulation capacity of bioactive molecules, and the average particle size of the prepared keratin nanoparticles loaded with bioactive molecules is 131-141 nm. Through the alginate-keratin-based double coating technology, spherical double-coated nanoparticles with regular shapes can be prepared, with an average particle size of 170-173nm, improved water solubility and environmental stability (such as heat treatment and low-temperature storage), and its responsive changes to gastrointestinal pH can significantly improve the stability of bioactive molecules, and can achieve cell delivery of bioactive molecules. The alginate-keratin-based double coating layer prepared by the invention has the encapsulation effect on both hydrophilic molecules (insulin) and hydrophobic molecules (resveratrol), and can be widely used in the encapsulation and delivery of bioactive molecules, including but not limited to oral nano delivery systems. The preparation method of the invention simplifies the preparation process of nanoparticles loaded with bioactive molecules, improves production efficiency, and does not involve chemical reagent pollution.

[0053] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.

Claims

1. A method for preparing stability-enhanced alginate-keratin-based double-coated nanoparticles, characterized in that: The steps include: Step 1: keratin is degraded by controlled enzymes, inactivated, centrifuged, and freeze-dried to obtain self-assembled keratin nanoparticles; Step 2: dispersing the keratin nanoparticles obtained in step 1 in an acidic buffer for structural development, adding bioactive molecules, stirring, and adjusting the pH value to neutral to allow the keratin structure to be reorganized and closed to obtain a keratin nanoparticle solution loaded with bioactive molecules; Step 3: Disperse the keratin nanoparticles loaded with bioactive molecules obtained in step 2 in a sodium alginate solution, add a calcium chloride solution dropwise to cross-link to form a calcium alginate shell after mixing evenly, dialyze or centrifuge to remove free bioactive molecules, and freeze-dry to obtain alginate-keratin double-coated nanoparticles loaded with bioactive molecules.

2. The preparation method according to claim 1, characterized in that Step 1 specifically includes: S11, evenly dispersing keratin in phosphate buffer, stirring for 12 to 16 hours for full hydration, adjusting the pH to 8.5, the temperature to 50 to 60 °C, the enzyme dosage to 5000-8000 U / g, and controlling the degree of hydrolysis to 5 to 15% for enzymatic degradation; S12. After the enzymatic hydrolysis, heat at 95°C for 3 min to inactivate the enzyme, adjust the pH to 7.0, centrifuge at 6000-8000 × g for 20-30 min, and freeze-dry to obtain self-assembled keratin nanoparticles.

3. The preparation method according to claim 1, characterized in that: Step 2 specifically includes: S21, dispersing the keratin nanoparticles obtained in step 1 in a phosphate buffer solution with a pH of 1.5 to 3.0, and stirring at 600 to 800 rpm for 1 to 2 h to develop the structure; S22, adding bioactive molecules, continuing stirring for 1 to 2 hours, adjusting the pH to 7.0, and continuing stirring for 1 to 2 hours to reorganize and close the structure to form a keratin nanoparticle solution loaded with bioactive molecules.

4. The preparation method according to claim 1, characterized in that: Step three specifically includes: S31, adding the keratin nanoparticle solution loaded with bioactive molecules obtained in step 2 dropwise into an equal volume of a sodium alginate solution having a mass volume concentration of 1 to 3%, and continuously stirring for 1 to 2 hours to obtain a mixed solution; S32. Add the mixed solution dropwise into an equal volume of 2-10 mM calcium chloride solution, continue stirring for 1-2 h, remove free bioactive molecules by dialysis or centrifugation, and freeze-dry to obtain alginate-keratin-based double-coated nanoparticles loaded with bioactive molecules.

5. The preparation method according to claim 1, characterized in that: The bioactive molecule is insulin or resveratrol.

6. The preparation method according to claim 2, characterized in that: In S11, the temperature is 55°C and the enzyme dosage is 6000 U / g; in S12, freeze-drying specifically includes: freeze-drying the enzymatic supernatant at -76°C and 0.009 mbar for 72 h.

7. The preparation method according to claim 3, characterized in that: The mass ratio of keratin nanoparticles to bioactive molecules was 2:1 or 25:1, respectively.

8. The preparation method according to claim 4, characterized in that: S32 specifically includes: adding the mixed solution dropwise into an equal volume of 4 mM calcium chloride solution, stirring continuously at 700 rpm for 1 h, dialyzing with a dialysis bag with a molecular weight cutoff of 7 kDa to remove free bioactive molecules, the dialysis time is ≥36 h, and freeze-drying at -76°C and 0.009 mbar for 72 h to obtain alginate-keratin-based double-coated nanoparticles loaded with bioactive molecules.

9. Stability-enhanced alginate-keratin-based double-coated nanoparticles prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the stability-enhanced alginate-keratin-based double-coated nanoparticles according to claim 9 in preparing nano-delivery carriers for bioactive molecules.

Citation Information

Patent Citations

  • Resveratrol embedded peanut protein nano-particles and preparation method thereof

    CN105709238A

  • Preparation method of self-assembled protein nano-composite micelle

    CN106084256A

  • Preparation method of casein / sodium alginate compound micro-capsule

    CN107970227A

  • Feather keratin / sodium alginate microgel drug loading system, and preparation method and application thereof

    CN113304273A

  • Preparation method of curcumin-loaded soybean protein isolate nano delivery system

    CN118141103A

Cited By

  • Ultrasonic-assisted prepared resveratrol-protein nanoparticle intestinal targeting delivery system and preparation method thereof

    CN121154523A